Thermal characteristic of sintered Ag-Cu nanopaste for high-temperature die-attach application - Tan, K.S.; Wong, Y.H.; Cheong, K.Y. (2015)
In this work, thermal characteristic of silver-copper (Ag-Cu) nanopaste that consists of a mixture of nano-sized Ag and Cu particles and organic compounds meant for high-temperature die-attach application is reported. The Ag-Cu nanopaste was sintered at 380 degrees C for 30 min without the need of applying external pressure and the effect of Cu loading (20-80 wt) on the thermal properties was investigated in against of pure Ag nanopaste and pure Cu nanopaste. The results showed the specific heat of sintered Ag-Cu nanopaste was increased as the loading of Cu increased. For thermal conductivity and coefficient of thermal expansion (CTE) of sintered Ag-Cu nanopaste, a declining trend has been recorded with the increment of Cu loading. Overall, the sintered Ag-Cu nanopaste with 20 wt of Cu loading has demonstrated the best combination of thermal conductivity (K) and CTE (alpha), which were 159 W/m K and 13 x 10(-6)/K, respectively. It has proven that there was a strong correlation between the amount of pores and thermal properties of the nanopaste. The ratio of K/alpha is a performance index (M), which has shown a higher value (12.2 x 10(6) W/m) than most of the commonly used die-attach systems. Finally, the Ag-Cu nanopaste has demonstrated a melting point of 955 degrees C, which can be proposed as an alternative high-temperature die-attach material. (C) 2014 Elsevier Masson SAS. All rights reserved.